How does family-supportive supervision influence work-family conflict in China? The role of boundary control and empowerment-focused HRM. Issue 1 (1st January 2023) - Yu, Guilan; Meng, Ying; Zhou, Chengxu
ABSTRACT: Drawing on the conservation of resources theory, this study investigates the relationship between family-supportive supervision (FSS) and work-family conflict (WFC). Data from a sample of 240 employees from 60 teams in China were analysed. The empirical results indicated that FSS reduced WFC by prompting employees' boundary control. Empowerment-focused human resource management (EHRM) moderated the relationship between FSS and WFC, such that the relationship was stronger for employees when the team had higher EHRM practices. This study delineates how and when FSS reduces WFC by identifying the mechanism and boundary conditions.